Pelatihan Blended Learning Hypercontent with Hyperlink Menggunakan QR Code untuk Guru Sekolah Menengah Pertama sebagai Strategi Pembelajaran Matematika di Purwakarta - Turmudi Turmudi; Asep Syarif Hidayat; Widayanti Widayanti; Nana Diana; Aan Yuliyanto; Riska Nurhasanah; Ahmad Rizal Jalaludin (Universitas Muhammadiyah Semarang, 2022)
As we all know that the Covid-19 pandemic has paralyzed various aspects including education. In the field of education, learning habits are limited face-to-face and are required to apply strict health protocols. On the other hand, the ability of teachers to teach their field of study using online methods still has limitations, for example, the ability to design teaching materials and transfer learning using media is considered to be very limited. Training and improving teacher competence through blended learning and the use of hyper content with hyperlinks are seen as one of the solutions so that teachers can design teaching materials oriented to text and image processing by using QR Codes. The subject matter, whether text, images, graphics, diagrams, or models designed by the teacher, can be delivered by using hyper content and inserting links to being content on the internet such as YouTube, to enhance the knowledge supply of teachers and students. The training activities were carried out face-to-face at the New Building, UPI Campus in Purwakarta, involving 20 Junior High School Teachers and 18 Madrasah Tsanawiyah Teachers in Purwakarta Regency. The results of the activity show that the blended learning hyper content with hyperlink training can improve the ability of teachers in designing engaging, interactive digital modules or teaching materials that are rich in content that can be accessed online anytime and anywhere or printed and then scanned via QR Code when students want to access the provided learning content. Thus, blended learning hyper content with hyperlinks can be used as an effective solution in improving the ability of teachers to design teaching materials during the COVID-19 pandemic and the implementation of limited face-to-face learning.